Education, conflict and social cohesion - Tawil, Sobhi; Harley, Alexandra; Braslavsky, Cecilia; Unesco. International Bureau of Education (Paris Unesco, International Bureau of Education, 2004)
"The studies presented in this volume examine the role of educational policy change in social and civic reconstrution and the redefinition of national citizenship within the context of identity-based conflicts. The underlying assumption is that if educational change is to be a meaningful contribution to processes of national reconciliation and peace building in the context of civil strife, the complex linkages between schooling and conflict need to be explicitly recognised and explored."--Pref.
Preface by Cecilia Braslavsky.
Keywords: Education -- Developing countries; Social conflict; War and society; Citizenship -- Study and teaching -- Developing countries; Social values -- Study and teaching -- Developing countries